Henrician Homer: English Verse Translations from the Iliad and Odyssey, 1531–1545. (July 2022) - Colley, John
Abstract : Verse translations from the Iliad and Odyssey embedded in Thomas Elyot's Gouernour, Roger Ascham's Toxophilus, and Nicholas Udall's Apophthegmes might seem the poor cousins of longer and better-known Homer translations by poets such as George Chapman. But this article, which pays close literary-critical attention to Elyot's, Ascham's, and Udall's Homer translations, argues that they play an important and mostly untold part in a larger story concerning the translation of Homer into English, not to mention the vernacular translation of ancient Greek literature in England in the sixteenth century. These fragmentary translations reveal that early Tudor writers had a wider array of options in their methods of classical translation than has hitherto been appreciated. They also call for more nuanced consideration of the diverse intellectual, political, and literary contexts that spurred poetic innovation in late Henrician England.